2018
DOI: 10.1128/aac.01663-18
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Ceftobiprole Resistance among Clinical Methicillin-Resistant Staphylococcus aureus Isolates from a Hospital in Central Italy

Abstract: Ceftobiprole is a fifth-generation cephalosporin with activity against methicillin-resistant Staphylococcus aureus (MRSA). One-year surveillance at the Regional Hospital of Ancona (Italy) disclosed a 12% ceftobiprole resistance rate (12/102 isolates; MIC, ≥4 mg/liter). Epidemiological characterization demonstrated that the resistant isolates all belonged to different clones. Penicillin-binding protein (PBP) analysis showed substitutions in all PBPs and a novel insertion in PBP2a. The mecB and mecC genes were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…CP009361.1) revealed aa alterations in PBP1, PBP2, PBP3 and PBP4, even though none of these differences were within the functional transglycosylase or transpeptidase domains [1,2,66,67,68]. Since Morroni et al compared the PBPs of ceftobiprole-resistant MRSA isolates with the vancomycin-resistant mecA -carrying MRSA Mu50 [69], a comparison of our isolates with Mu50 (acc. no.…”
Section: Discussionmentioning
confidence: 99%
“…CP009361.1) revealed aa alterations in PBP1, PBP2, PBP3 and PBP4, even though none of these differences were within the functional transglycosylase or transpeptidase domains [1,2,66,67,68]. Since Morroni et al compared the PBPs of ceftobiprole-resistant MRSA isolates with the vancomycin-resistant mecA -carrying MRSA Mu50 [69], a comparison of our isolates with Mu50 (acc. no.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the mecC -MRSA human prevalence detected in most of the studies was very low. Several studies did not identify any mecC -positive S. aureus among included human isolates/samples ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In studies in which this gene was detected ( Table 1 ), the prevalence identified, considering the total number of isolates/samples included, was < 1% in most of the cases [ 24 , 27 , 28 , 29 , 32 , 33 , 37 , 40 , 41 , 42 , 43 ], similar to that identified in the first study in which mecC was discovered (approximately 0.04%) [ 16 ].…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…Of these, only the oxazolidinones, now nearly 20 years old, were a completely new class [9]. Clinical resistance has already been observed for all nine of these drugs, though it can be difficult to predict how quickly or widely some of these resistances will spread [10,11,12,13,14,15,16,17,18,19]. Side effects such as renal toxicity and cross-resistance (e.g.…”
Section: Introductionmentioning
confidence: 99%